1995
DOI: 10.1046/j.1365-313x.1995.7020245.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle‐regulated histone gene expression in synchronized plant cells

Abstract: SummaryThe regulation of histone gene expression during the cell cycle has been studied in a synchronized tobacco (BY2) cell suspension. Maximal expression was found in S phase but unlike other eukeryoti¢ organisms the amount of histone mRNA was not coupled to DNA synthesis. Using aphidicolin as an inhibitor of DNA synthesis either before or at mid-S phase an accumulation of histone mRNA= was found in the absence of any DNA synthesis which was not due to a stabilization of the mRNAs but to actual control at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 13 publications
6
65
0
2
Order By: Relevance
“…5). This behavior toward the two inhibitors was identical to that previously reported for histone genes and assumed to result from the arrest of the cell cycle by the two inhibitors at two different points, one (hydroxyurea) blocking before and the other (aphidicolin) blocking after the point of induction of these genes (13). The basal level of NtcycA19 mRNAs was unaffected by the aphidicolin treatment but decreased upon hydroxyurea treatment (Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…5). This behavior toward the two inhibitors was identical to that previously reported for histone genes and assumed to result from the arrest of the cell cycle by the two inhibitors at two different points, one (hydroxyurea) blocking before and the other (aphidicolin) blocking after the point of induction of these genes (13). The basal level of NtcycA19 mRNAs was unaffected by the aphidicolin treatment but decreased upon hydroxyurea treatment (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Measurement of DNA synthesis, mitotic index, and isolation of RNA were as in ref. 13. Total RNA (25 g) was electrophoresed on formaldehyde͞agarose gels and transferred to Hybond-N membranes (Amersham).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, most key regulators of the (supposedly more distant) animal cell cycle seem to be conserved in higher plants. The occurrence of cyclins and cyclin-dependent protein kinases in higher plants similar to those found in animals is now well established (Ferreira et al, 1991(Ferreira et al, , 1994Hemerly et al, 1992 ;Reichheld et al, 1995Reichheld et al, , 1996, and retinoblastoma protein homologues (Murray, 1997 ;Murray et al, 1997 ;Huntley et al, 1997) and cdc25 homologues (Sabelli et al, 1998) have been isolated recently. Given this overall conservation of cell cycle machinery and circumstantial evidence such as the fact that in a number of cyclins the primary structure reveals signatures for post-translational modifications dependent on cAMP (analogous to cyclin D " ), the observation made by Ehsan et al (1998) demands a further search for a role for cAMP in the plant cell cycle.…”
Section:    C mentioning
confidence: 84%
“…Similar results indicating that the levels of DNA synthesis and gene expression are uncoupled were also reported in A3-type cyclins. Reichheld et al (1995Reichheld et al ( , 1996 reported that the expression of NtcycA59 and NtcycA105 (renamed Nicta;CycA3;1 and Nicta;CycA3;2, respectively; reviewed by Hemerly et al 1999) was not N. Suda et al suppressed by the addition of aphidicolin to tobacco BY-2 cells in the stationary phase, even though DNA synthesis rates decreased. This suggests that the expression level of A3-type cyclin genes and the level of DNA synthesis are not always correlated.…”
Section: Discussionmentioning
confidence: 99%